Thermoplastic elastomer composition

A thermoplastic elastomer composition using magnesium carbonate and zinc oxide fillers with varying particle sizes addresses the balance of thermal conductivity, insulation, and hardness, enhancing performance and reducing equipment wear in electronic device applications.

JP7608197B2Active Publication Date: 2025-01-06NOK CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021020199
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-10
Publication Date
2025-01-06
Estimated Expiration
2041-02-10

AI Technical Summary

Technical Problem

Existing thermally conductive materials face challenges in achieving a balance of thermal conductivity, insulation properties, and hardness while minimizing the load on manufacturing equipment, with fillers like aluminum nitride being unstable, aluminum oxide having high hardness, magnesium oxide absorbing moisture, and beryllium oxide being expensive and hazardous.

Method used

A thermoplastic elastomer composition is developed using a blend of two types of magnesium carbonate with different particle sizes and zinc oxide, optimizing the volume ratios to achieve low hardness, excellent thermal conductivity, and insulation properties, thereby reducing the load on manufacturing equipment.

Benefits of technology

The composition achieves a well-balanced performance with low hardness, high thermal conductivity, and insulation properties, suitable for applications in electronic devices and circuit boards, while minimizing equipment wear.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608197000001
    Figure 0007608197000001
  • Figure 0007608197000002
    Figure 0007608197000002
Patent Text Reader

Abstract

To provide a thermoplastic elastomer composition low in hardness, excellent in thermal conductivity and insulation property, and low in load to a production apparatus.SOLUTION: A thermoplastic elastomer composition is obtained by blending a thermoplastic elastomer with a thermally conductive filler, in which the thermally conductive filler includes two types of magnesium carbonate having an average particle size of 0.3 to 5 μm and 7 to 60 μm, and zinc oxide having an average particle size of 0.3 to 5 μm, has JIS durometer hardness A of 80 or smaller, and thermal conductivity of 1.5 W / m K or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic elastomer composition having excellent thermal conductivity. [Background technology]

[0002] Thermally conductive materials are used in a variety of applications, including as sealing materials for semiconductor chips mounted on personal computers and mobile phones, and as heat dissipation materials for circuit boards in electronic devices such as car-mounted cameras. Furthermore, these applications require insulation as well as thermal conductivity, so the selection of fillers to be mixed into the material is extremely important.

[0003] The thermal conductivity of thermally conductive materials is usually achieved by adding thermally conductive fillers such as aluminum oxide, graphite, beryllium oxide, zinc oxide (zinc oxide), magnesium oxide, boron nitride, and aluminum nitride to the material.

[0004] However, while nitrides such as aluminum nitride and boron nitride have good thermal conductivity, they are expensive. Aluminum nitride, in particular, is an unstable material that is prone to hydrolysis, making it a difficult filler to handle. Aluminum oxide is stable and has relatively good thermal conductivity, but its Mohs hardness is very high at 9, which raises concerns about the load on manufacturing equipment (main metal: iron, Mohs hardness 5). Magnesium oxide has excellent thermal conductivity among oxides, but it has a tendency to absorb moisture, making it difficult to achieve stable performance. Various methods for surface treatment of magnesium oxide have been investigated, but no satisfactory method has been found. Beryllium oxide has excellent thermal conductivity, but is expensive and requires careful handling because it is classified as a Type 1 specified chemical substance. Silica is widely used as a filler for sealing materials, but has poor thermal conductivity.

[0005] As an alternative to the above-mentioned fillers, Patent Document 1 discloses magnesium carbonate filler. According to Patent Document 1, magnesium carbonate filler having a BET specific surface area of ​​0.1 to 10 m 2This paper discloses a synthetic resin composition and a synthetic rubber composition in which 100 to 600 parts by weight of magnesium carbonate filler having an average particle size of 1 to 50 μm is blended with 100 parts by weight of synthetic resin or synthetic rubber. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2006-291078 A Summary of the Invention [Problem to be solved by the invention]

[0007] Patent Document 1 discloses that magnesium carbonate can impart thermal conductivity, flame retardancy, processability, etc. However, it is unclear whether it can impart insulating properties to the composition, and there is still room for improvement in thermal conductivity and hardness.

[0008] The present invention has been made in view of the above circumstances. That is, an object of the present invention is to provide a thermoplastic elastomer composition that has low hardness, excellent thermal conductivity and insulating properties, and imposes a small load on production equipment. [Means for solving the problem]

[0009] In order to solve the above problems, the present inventors focused on magnesium carbonate and zinc oxide as fillers for thermoplastic elastomers. By blending two types of magnesium carbonate with different particle sizes and further using zinc oxide in combination, they succeeded in obtaining a thermoplastic elastomer composition with an excellent balance of physical properties, and thus completed the present invention. That is, the present invention has the following configuration.

[0010] Thermoplastic elastomer with thermally conductive filler 50~62vol%The thermoplastic elastomer composition contains, as the thermally conductive filler, two types of magnesium carbonate having an average particle size of 0.3 to 5 μm and 7 to 60 μm, and zinc oxide having an average particle size of 0.3 to 5 μm, a volume ratio of the magnesium carbonate having an average particle diameter of 0.3 to 5 μm to the magnesium carbonate having an average particle diameter of 7 to 60 μm is 20 / 80 to 70 / 30, and a volume ratio of the sum of the magnesium carbonate having an average particle diameter of 0.3 to 5 μm and the zinc oxide to the magnesium carbonate having an average particle diameter of 7 to 60 μm is 35 / 65 to 77 / 23, The thermoplastic elastomer composition is characterized by having a JIS durometer type A hardness of 80 or less and a thermal conductivity of 1.5 W / m·K or more. Effect of the Invention

[0011] The thermoplastic elastomer composition of the present invention has low hardness, is excellent in thermal conductivity and electrical insulation, and imposes a low load on production equipment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, embodiments of the present invention will be described in detail. However, the scope of the present invention is not limited to the specific embodiments described below.

[0013] The thermoplastic elastomer composition of the present embodiment contains two types of magnesium carbonate and zinc oxide having different average particle sizes as a thermally conductive filler in a thermoplastic elastomer. Each component constituting the thermoplastic elastomer composition of the present embodiment will be described below.

[0014] (Thermoplastic elastomer) The thermoplastic elastomer is not particularly limited, but is preferably one that can be used as a sealing material or a heat dissipation material. Examples of the types of thermoplastic elastomer include olefin-based, styrene-based, amide-based, ester-based, vinyl chloride-based, and urethane-based. Among these, styrene-based thermoplastic elastomers are preferred. The thermoplastic elastomer can be appropriately selected from commercially available products. Since the thermoplastic elastomer of this embodiment is made into a composition by adding a large amount of thermally conductive filler, it is preferred that the thermoplastic elastomer has a relatively low hardness, excellent mechanical properties and processability, and excellent affinity with the thermally conductive filler.

[0015] (Magnesium Carbonate) Magnesium carbonate is a carbonate salt of magnesium, and is a stable compound with water resistance. Magnesium carbonate exists as anhydrous, dihydrate, trihydrate, and pentahydrate. Magnesium carbonate is a tasteless, odorless, white powder, and can be manufactured in various particle sizes. In addition, since magnesium carbonate has a Mohs hardness of 3.5, there is little concern about the load on manufacturing equipment that uses iron, which has a Mohs hardness of 5.

[0016] Furthermore, magnesium carbonate has excellent thermal conductivity with a thermal conductivity of 15 W / m K and a volume resistivity of 10 14 Therefore, the present inventors have investigated magnesium carbonate as a filler for imparting thermal conductivity and insulating properties to thermoplastic elastomers.

[0017] The thermal conductivity of a thermoplastic elastomer composition is increased by adding magnesium carbonate particles to the thermoplastic elastomer. However, when the amount of magnesium carbonate is increased, the hardness of the thermoplastic elastomer composition increases, making it difficult to use the composition as a sealing material or a heat dissipation material. Therefore, we investigated the use of magnesium carbonate particles with different particle sizes.

[0018] By considering the addition of at least two types of magnesium carbonate with different average particle sizes to a thermoplastic elastomer, it was found that it is possible to produce a thermoplastic elastomer composition that has stable performance, such as not being hydrolyzed or absorbing moisture, and that also has thermal conductivity and insulating properties and low hardness.

[0019] When magnesium carbonate particles with different particle sizes are used in combination, the small particle size particles are densely packed into the gaps between the large particle size particles, which makes it possible to suppress an increase in hardness and to satisfy both thermal conductivity and insulation properties compared to when only large particle size magnesium carbonate or only small particle size magnesium carbonate is added.

[0020] (Zinc Oxide) Zinc oxide is a white powder also known as zinc white or zinc oxide. Zinc oxide has a small particle size, excellent water resistance, and low toxicity. Zinc oxide also has a thermal conductivity of 54 W / m·K, which is far superior to that of magnesium carbonate. Zinc oxide also has a Mohs hardness of 4, so there is little concern about the load on manufacturing equipment that uses iron, which has a Mohs hardness of 5. However, since zinc oxide has a relatively small volume resistivity, there is a concern that its insulating properties may decrease if it is mixed in large quantities.

[0021] Therefore, in order to further improve the thermal conductivity of the thermoplastic elastomer, the present inventors investigated the blending of zinc oxide as fine particles with a small particle size in addition to two types of magnesium carbonate with different particle sizes.

[0022] As a result, by combining two types of magnesium carbonate, one with a large particle size and one with a small particle size, with small particle size zinc oxide as a thermally conductive filler in a thermoplastic elastomer, they succeeded in obtaining a thermoplastic elastomer composition that satisfies both thermal conductivity and insulation properties in a well-balanced manner.

[0023] The small particle size magnesium carbonate has an average particle size of 0.3 to 5 μm, preferably 0.5 to 4 μm, and more preferably 0.7 to 3 μm. On the other hand, the large particle size magnesium carbonate has an average particle size of 7 to 60 μm, preferably 10 to 50 μm, and more preferably 15 to 40 μm. Furthermore, the zinc oxide has an average particle size of 0.3 to 5 μm, preferably 0.5 to 4 μm, and more preferably 0.7 to 3 μm. The average particle size of magnesium carbonate and zinc oxide can be measured in accordance with JIS Z 8825:2013.

[0024] Here, magnesium carbonate with an average particle size of 0.3 to 5 μm may be referred to as "small particle magnesium carbonate," magnesium carbonate with an average particle size of 7 to 60 μm may be referred to as "large particle magnesium carbonate," and zinc oxide with an average particle size of 0.3 to 5 μm may be referred to as "small particle zinc oxide."

[0025] In view of the balance of the hardness, thermal conductivity, and insulating properties of the thermoplastic elastomer composition, the volume ratio of the total of small particle size magnesium carbonate and zinc oxide to large particle size magnesium carbonate is preferably 35 / 65 to 77 / 23, and more preferably 50 / 50 to 60 / 40.

[0026] In addition, in view of the balance of the hardness, thermal conductivity, and insulating properties of the thermoplastic elastomer composition, the volume ratio of small particle size magnesium carbonate to large particle size magnesium carbonate is preferably 20 / 80 to 70 / 30, and more preferably 30 / 70 to 50 / 50.

[0027] From the viewpoint of the balance of the hardness, thermal conductivity, and insulating properties of the thermoplastic elastomer composition, the thermoplastic elastomer composition preferably contains 50 vol% or more of a thermally conductive filler containing magnesium carbonate and zinc oxide. The total content of the thermally conductive filler is more preferably 50 to 62 vol%, and even more preferably 53 to 58 vol%, relative to 100 vol% of the thermoplastic elastomer composition.

[0028] (Thermoplastic elastomer composition) The thermoplastic elastomer composition of the present embodiment may contain a thermoplastic resin other than the thermoplastic elastomer, as long as the effect of the present invention is not impaired. In addition, various known additives may be appropriately added to the thermoplastic elastomer composition of the present embodiment. Examples of known additives include reinforcing agents, inorganic fillers, plasticizers, softeners, antioxidants, processing aids, crosslinking agents, crosslinking assistants, crosslinking accelerators, dispersing assistants, foaming agents, foaming assistants, colorants, flame retardants, tackifiers, and release agents.

[0029] The thermoplastic elastomer composition has a JIS durometer type A hardness of 80 or less in accordance with JIS K 6253. When the thermoplastic elastomer composition has a JIS durometer type A hardness of 80 or less, the thermoplastic elastomer composition can be used in a wide range of applications, such as a sealing material for electronic devices and a heat dissipation material.

[0030] The thermal conductivity of the thermoplastic elastomer composition is 1.5 W / m K or more, and preferably 2.0 W / m K or more. If the thermal conductivity is 1.5 W / m K or more, the thermoplastic elastomer composition can be used in a wide range of applications, such as sealing materials and heat dissipation materials for electronic devices. Thermal conductivity can be measured in accordance with ASTM D7984.

[0031] The thermoplastic elastomer composition has a volume resistivity of 1×10 10 It is preferable that the volume resistivity is 1×10 Ω·cm or more. 10 If the resistivity is Ω·cm or more, the thermoplastic elastomer composition can be used in a wide range of applications, such as sealing materials and heat dissipation materials for electronic devices, etc. The volume resistivity can be measured in accordance with JIS K6271-1:2015.

[0032] The thermoplastic elastomer composition preferably has a specific gravity of 2 to 3. When the thermoplastic elastomer composition is used for a wide range of applications such as a sealing material or a heat dissipation material for electronic devices, the specific gravity is preferably light, ie, 3 or less.

[0033] The thermoplastic elastomer composition of the present embodiment has low hardness, is stable without hydrolysis or moisture absorption, and has excellent insulating properties and thermal conductivity. In addition, the thermoplastic elastomer composition of the present embodiment contains a thermally conductive filler having a Mohs hardness of less than 5, so that the load on the equipment is small.

[0034] (Manufacturing method) The thermoplastic elastomer composition of the present embodiment can be produced by kneading the raw materials by a known method. Known production equipment includes, for example, a twin-screw extruder, a lab plastomill, a Banbury mixer, a kneader, a planetary mixer, an intermix, a two-roll machine, a three-roll machine, and the like. Predetermined raw materials are kneaded and molded into a predetermined shape by injection molding or the like using a predetermined mold. In some cases, crosslinking may be performed using a crosslinking agent. In that case, after preparing an uncrosslinked thermoplastic elastomer composition, crosslinking is performed by heating using a crosslinking press, a compression molding machine, an injection molding machine, or the like. If necessary, secondary crosslinking can also be performed. By the above crosslinking, a crosslinked molded product of the thermoplastic elastomer composition can be obtained.

[0035] The thermoplastic elastomer composition of the present embodiment has low hardness and excellent thermal conductivity and insulating properties, and therefore can be suitably used as a sealing material for semiconductor chips and the like mounted on electronic devices, automobiles, general industrial machines, etc., and a heat dissipation material for circuit boards for electronic devices, automobiles, general industrial machines, etc. EXAMPLES

[0036] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.

[0037] (Examples 1 to 7, Comparative Examples 1 to 8) The materials used in the examples are as follows: (i) Thermoplastic elastomer: styrene-based thermoplastic elastomer, manufactured by Aronkasei Co., Ltd., AR-710N, low hardness grade (JIS durometer hardness, type A hardness 7) (ii) Magnesium carbonate: manufactured by Konoshima Chemical Co., Ltd., Magthermo MS-PS (average particle size: 21 μm), Magthermo MS-S (average particle size: 1.2 μm) (iii) Zinc oxide: manufactured by Seido Chemical Industry Co., Ltd., zinc oxide type 1, JIS K1410, sieve residue of 0.1% or less

[0038] (Preparation of test pieces for measuring characteristics) The mixture was kneaded using a Labo Plastomill and an injection molding machine, and the thermoplastic elastomer compositions having the compositions shown in Tables 1 and 2 were molded into thermoplastic elastomer composition sheets having a thickness of 2 mm.

[0039] <Evaluation items> (Normal physical properties) The thermoplastic elastomer composition sheet was evaluated for the following normal state physical properties. Hardness: Measured using a durometer type A in accordance with JIS K 6253. Specific gravity: Measured in accordance with JIS K 6268.

[0040] (Thermal Conductivity) The thermal conductivity (W / m·K) of the thermoplastic elastomer composition sheet was measured in accordance with ASTM D7984.

[0041] (Volume resistivity) The volume resistivity (Ω·cm) of the thermoplastic elastomer composition sheet was measured in accordance with JIS K6271-1:2015.

[0042] The evaluation results are shown in Tables 1 and 2. In Tables 1 and 2, for example, the volume resistivity of 3.8E+11Ω·cm in Example 1 is 3.8×10 11 This means Ω cm. The same applies below.

[0043] [Table 1]

[0044] [Table 2]

[0045] As can be seen from the results in Tables 1 and 2, the thermoplastic elastomer compositions of Examples 1 to 7 had a durometer hardness of 80 or less, a thermal conductivity of 1.5 W / m K or more, and a volume resistivity of 1×10 10The thermoplastic elastomer compositions of Comparative Examples 1, 6, and 7 had a thermal conductivity of less than 1.5 W / m K, and thus exhibited poor thermal conductivity. The thermoplastic elastomer compositions of Comparative Examples 2 to 5, and 8 had a durometer hardness of more than 80, and thus exhibited high hardness.

Claims

1. A thermoplastic elastomer composition comprising a thermoplastic elastomer and 50 to 62 vol% of a thermally conductive filler, The thermally conductive filler contains two types of magnesium carbonate having an average particle size of 0.3 to 5 μm and 7 to 60 μm, and zinc oxide having an average particle size of 0.3 to 5 μm, a volume ratio of the magnesium carbonate having an average particle size of 0.3 to 5 μm to the magnesium carbonate having an average particle size of 7 to 60 μm is 20 / 80 to 70 / 30; a volume ratio of the sum of the magnesium carbonate and the zinc oxide having an average particle size of 0.3 to 5 μm to the magnesium carbonate having an average particle size of 7 to 60 μm is 35 / 65 to 77 / 23; JIS durometer hardness type A is 80 or less, Thermal conductivity is 1.5 W / m・K or more A thermoplastic elastomer composition comprising:

2. The thermoplastic elastomer composition according to claim 1 , wherein the thermally conductive filler comprises a thermally conductive filler having a Mohs hardness of less than 5.

3. Volume resistivity is 1×10 10 The thermoplastic elastomer composition according to claim 1 or 2, having a modulus of Ω·cm or more.

4. The thermoplastic elastomer composition according to any one of claims 1 to 3, which is used for a sealing material or a heat dissipating material.

Citation Information

Patent Citations

  • Filler and manufacturing method of it, synthetic resin composition and synthetic rubber composition

    JP2006291078A

  • Heat radiation material and heat radiation sheet formed of heat radiation material

    JP2008163145A

  • Die-bonding material for optical semiconductor device and optical semiconductor device using the same

    JP2012049567A

  • Resin composition

    JP2012102202A

  • Heat-conductive resin composition and molded body

    JP2014159554A